Perbedaan Pengaruh Metode Latihan Squat Jump dan Split Squat Jump terhadap Peningkatan Power Otot Tungkai - M. Adi Dwi Mutaqin; Pipit Fitria Yulianto; Bagus Kuncoro (SPRINTER: Jurnal Ilmu Olahraga, 2025)
The purpose of this study was to determine the differences in the effects of plyometric squat jump and split squat jump training methods on leg muscle power improvement in male athletes aged 11-13 years at SSB Satria Utama Jumantono, Karanganyar in 2025. The research sample consisted of 30 students from the SSB Satria Utama Jumantono club in Karanganyar. Sampling was conducted using random sampling techniques. The research variables were the test results and measurements of leg muscle power improvement with the influence of plyometric squat jump and split squat jump training as independent variables and leg muscle power improvement as a dependent variable. The research design used a pretest-posttest design. Tests to determine the increase in leg muscle power used tests and measurements of leg muscle power ability. The research data analysis method used the t-test formula calculated using a short formula. The results of the data analysis led to the following conclusions: (1) There was a significant difference between the effects of the Plyometric Squat Jump and Plyometric Split Squat Jump methods on the increase in leg muscle power in volleyball among male athletes aged 11-13 years at SSB Satria Utama Jumantono, Karanganyar in 2025. This is evidenced by the results of the final test calculations for each group, namely tcount = 2.816, which is smaller than ttable = 2.145 with a significance level of 5%. (2) The Plyometric Squat Jump method has a better effect than the Plyometric Split Squat Jump method on improving leg muscle power in volleyball among 11-13-year-old male athletes at SSB Satria Utama Jumantono, Karanganyar in 2025. Based on the percentage increase in leg muscle power in soccer, group 1 (the group treated with the Plyometric Squat Jump method) showed a 6.499% increase, while group 2 (the group treated with the Plyometric Split Squat Jump method) showed a 5.684% increase.